Activation of peroxymonosulfate by magnetic Fe3S4/biochar composites for the efficient degradation of 2, 4, 6-trichlorophenol: Synergistic effect and mechanism. Issue 1 (February 2022) - Li, Hui; Li, Siyang; Jin, Lide; Lu, Zhen; Xiang, Minghui; Wang, Chen; Wang, Wenbing; Zhang, Jin; Li, Chunyang; Xie, Haijiao
Abstract: The synergistic catalytic degradation of metal carbon-based composites is a feasible strategy to improve the efficiency of advanced oxidation processes (AOPs) by means of green chemistry. In this work, Fe3 S4 nanoparticles were anchored on the surface of peanut shell biochar to prepare magnetic Fe3 S4 /biochar (Fe3 S4 /BC) composites, which were applied to activate peroxymonosulfate (PMS) to degrade 2, 4, 6-trichlorophenol (2, 4, 6-TCP). The addition of biochar not only reduced the aggregation of Fe3 S4 nanoparticles, but also accelerated the electron transfer rate, and the constructed C-O-Fe bridges accelerated the regeneration of Fe(Ⅱ), which made Fe3 S4 /BC have better catalytic performance than pure Fe3 S4 even though the use of metal sulfides was reduced. Fe on the surface of Fe3 S4 /BC was the catalytic reaction center. The dominant role of sulfate radical (SO4 ·- ) and hydroxyl radical (HO·) on the degradation of 2, 4, 6-TCP was verified by electron paramagnetic resonance (EPR) and free radical quenching experiments. The mechanism of C-O-Fe bridges was verified by density functional theory (DFT) calculation. The mechanism of PMS activation by Fe3 S4 /BC was elucidated by electrochemical impedance spectroscopy (EIS) and X-ray photoelectron spectroscopy (XPS). Based on the detection results of intermediate products, the possible degradation pathways to 2, 4, 6-TCP were proposed. This work provides new insights into the synergistic catalytic mechanism of metal carbon-based sulfides and promotes the development of environmentally friendly and efficient metal carbon-based catalysts. Graphical Abstract: ga1 Highlights: The Fe3 S4 /BC exhibited superior catalytic performance to the pure Fe3 S4 . BC improved dispersion of Fe3 S4 nanoparticles and accelerated electron transfer. Fe 3+ /Fe 2+ cycle was facilitated by reducing sulphur species and C-O-Fe bridges. The Fe3 S4 /BC/PMS system is suitable for a wide pH range. Both SO4 ·- and HO· were responsible for 2, 4, 6-TCP degradation, especially SO4 ·- .